High-efficiency Thulium-doped fiber laser at 1.7 μm. (August 2022) - Zhang, Lu; Zhang, Junxiang; Sheng, Quan; Fu, Shijie; Shi, Wei; Yao, Jianquan
Highlights: An efficient 1.7 μm all-fiber laser is achieved based on commercial Tm-doped silica fiber. With an optimized cavity design, the laser yields a recorded power of 5.92 W with a slope efficiency of 64%. A high optical signal to noise ratio (OSNR) of 66 dB is realized. A rate equation model is developed to investigate the potential power scaling. Abstract: An efficient Tm-doped fiber laser was demonstrated at the wavelength region of 1.7 μm, which wavelength was ever considered as an obstacle for efficient laser generation with Tm-doped fiber due to the serious re-absorption effect. In this work, bi-directional pump at 1570 nm was employed for sufficient pump absorption, and gain fiber length was optimized to decrease re-absorption loss of signal light and suppress amplified spontaneous emission in the 1.8–2 μm region. A maximum output power of 5.92 W at 1720 nm was achieved in experiment, corresponding to a slope efficiency with respect to the launched pump power of 64%. Numerical simulation was also implemented to investigate the further output power optimization. This work shows that a high 1.7 μm laser efficiency, which is comparable with that achieved with the special homemade Tm-doped fiber, can be realized by using the commercial silica Tm-doped fiber.